Development of Un-Tensioned Pullout Tests to Determine the Bond Quality of Prestressing Reinforcements Used in Pretensioned Concrete Railroad Ties - Arnold, Matthew L.; Peterman, Robert J.; Beck, B. Terry; Wu, Chih-Hang (Rural Railroad Safety Center, Kansas State University., 2021)
An experimental program was conducted at Kansas State University (KSU) to evaluate the bond characteristics of prestressing wires and strands used in the manufacture of pretensioned concrete railroad ties. Un-tensioned pullout tests were conducted using both concrete and mortar mediums. The effect of prestressing steel surface condition on bond was evaluated by testing the bond in both the as-received and cleaned condition. A pullout test was developed (and subsequently adopted as ASTM A1096) that can be used to determine the bond quality of prestressing wires that are are in pretensioned concrete members. The pullout test specimens consist of a 4 in. outer-diameter tube with a total length of 8 in. and a steel plate welded to the tube bottom. An un-tensioned wire is held concentrically in the tube while a sand-cement mortar mixture is placed and allowed to cure. Specimens are tested when compressive strength of the mortar is between 4500 and 5000 psi. Pullout test results had excellent correlation with transfer lengths of similar wires when used to manufacture pretensioned concrete railroad ties.
Keywords: ASTM A1096; Wire Bond; Un-Tensioned Pullout Tests; Bond Slip; Railroad Ties; Prestressed Concrete